A Study on Information Visualization in the Form of Interactive Art Focused on Protection of Sensitive Data - Kim, Kyoung-Nam; Kim, Jung-Yoon (Journal of Next-generation Convergence Information Services Technology, 2019)
Information visualization, which expresses information analysis results is an easy-to-understand manner, is useful for capturing and conveying information at a glance. However, in the field of information visualization, care must be taken when providing information that contains sensitive information, such as sex offenses. For example, if you provide visualized information on the areas where sex crimes often occur to promote people's safety based on only clarity and accuracy to provide information, you might reduce the value of the real estate in that area, and compromise the privacy of individuals, causing a secondary social problem. Therefore, we tried to integrate information visualization with interactive art as a complementary information visualization method that can provide information to people while protecting sensitive information. Herein, we studied how to visualize the information through phased visualization of the interactive art and application of aesthetic elements of the art. KCI Citation Count: 0